2008
DOI: 10.1007/s11706-008-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure and development of the collar enamel in gars, Lepisosteus oculatus, Actinopterygii

Abstract: The fine structure of collar enamel and the cells constituting the enamel organ during amelogenesis in Lepisosteus oculatus was observed by light, scanning electron and transmission electron microscopy. In the enamel, slender crystals were arranged perpendicular to the surface and the stripes that were parallel to the surface were observed, suggesting that the enamel in Lepisosteus shares common morphological features with that in sarcopterygian fish and amphibians. Ameloblasts containing developed Golgi appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The morphological features of the collar enamel in Polypterus closely resemble those of the collar enamel in Lepisosteus (Sasagawa et al 2008) and of the non-prismatic enamel in lungfish, coelacanths and amphibians (Schmidt and Keil 1971;Smith and Miles 1971;Shellis and Poole 1978;Smith 1978;Sasagawa et al 1984;Satchell et al 2000). However, the collar enamel layer in Polypterus (500 nm to 1 μm) is thin in comparison with those found in Lepisosteus (5 μm; Sasagawa et al 2008) and in lungfish, coelacanths and amphibians (6-8 μm; Smith and Miles 1971;Sasagawa et al 1984;Satchell et al 2000). In addition, the collar enamel in Polypterus is probably only produced in a limited area of the tooth shaft near to the cap enameloid.…”
Section: Collar Enamel Is Present At the Surface Of The Tooth Shaft Imentioning
confidence: 67%
See 1 more Smart Citation
“…The morphological features of the collar enamel in Polypterus closely resemble those of the collar enamel in Lepisosteus (Sasagawa et al 2008) and of the non-prismatic enamel in lungfish, coelacanths and amphibians (Schmidt and Keil 1971;Smith and Miles 1971;Shellis and Poole 1978;Smith 1978;Sasagawa et al 1984;Satchell et al 2000). However, the collar enamel layer in Polypterus (500 nm to 1 μm) is thin in comparison with those found in Lepisosteus (5 μm; Sasagawa et al 2008) and in lungfish, coelacanths and amphibians (6-8 μm; Smith and Miles 1971;Sasagawa et al 1984;Satchell et al 2000). In addition, the collar enamel in Polypterus is probably only produced in a limited area of the tooth shaft near to the cap enameloid.…”
Section: Collar Enamel Is Present At the Surface Of The Tooth Shaft Imentioning
confidence: 67%
“…In extant actinopterygians, collar enamel has only been described in Lepisosteus (gars), once by electron microscopy (Prostak et al 1989) and twice by immunohistochemistry (Ishiyama et al 1999). In Lepisosteus, morphological data suggest that collar enamel shares common features with those of the enamel found in sarcopterygians and amphibians (Sasagawa et al 2008). Immunohistochemical observations have indicated that the enamel matrix in Lepisosteus contains domains that closely resemble those occurring in mammalian amelogenins, whereas immunoblot studies have demonstrated that the amelogenins of mammals are not present in the enamel proteins of Lepisosteus (I.…”
mentioning
confidence: 99%
“…In the enamel layer, slender crystallites are arranged perpendicular to the surface, but do not make marked bundles (aprismatic enamel). Several stripes that lie almost parallel to the surface are usually observed in the section, implying that the stripes are incremental lines and indicating centrifugal growth [32,33,[37][38][39]44,45] (Fig. 6).…”
Section: The Morphological Features Of Enamel In Fishmentioning
confidence: 94%
“…Collar enamel was initially noted in fossilized actinopterygians [32,33] and has also been reported in some living species, including Lepisosteus and Polypterus [34][35][36][37] (Figs. 5 and 6).…”
Section: The Morphological Features Of Enamel In Fishmentioning
confidence: 98%
See 1 more Smart Citation